Mapping the Intellectual Structure of Digital Library Research:A Bibliometric Analysis of Global Publications (2010–2025) - Endang Fatmawati; Jazimatul Husna; Minan Faiz Fausta Rafa (Pustabiblia: Journal of Library and Information Science, 2026)
Background: Digital library research has experienced exponential growth since 2010, yet no comprehensive bibliometric study has systematically mapped its global intellectual structure. Objective: This study aims to analyze 14,876 publications indexed in Web of Science (WoS) and Scopus from 2010 to 2025, employing advanced bibliometric methodologies to identify leading contributors, key research themes, intellectual clusters, and future trajectories. Methods: We employed performance analysis and science mapping techniques including co-citation analysis, keyword co-occurrence analysis, bibliographic coupling, and co-authorship network analysis. Software tools including VOSviewer, Bibliometrix (R-package), and CiteSpace were utilized for visualization. Results: The United States (n = 4,231), China (n = 3,876), and the United Kingdom (n = 2,145) emerged as the most productive nations. The Journal of the Association for Information Science and Technology (JASIST) led in citations. Six major thematic clusters were identified: (1) Information Retrieval & Search Systems, (2) User Experience & Usability, (3) Digital Preservation & Metadata, (4) Open Access & Scholarly Communication, (5) Semantic Web & Linked Data, and (6) Artificial Intelligence & Machine Learning applications. Conclusion: The field is shifting from traditional cataloging and retrieval paradigms toward AI-driven, user-centric, and interoperable architectures. Emerging themes include federated learning for privacy-preserving recommendation systems and large language model integration in digital curation workflows